Botswana : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report presents an assessment of public investment management in Botswana. Botswana's public investment has been consistently high for the past 25 years coupled with prudent fiscal policy and moderate debt at about 10 percent of GDP. Relatively high public investment spending has contributed to steady accumulation of capital stock-almost three times more per capita than peers and emerging market averages. More than 60 percent of investment is spent on economic affairs. While Botswana performed better than peer and emerging market averages up to 2010, more recently, indicators of infrastructure quality suggest significant bottlenecks, particularly in access to electricity supply and railways.